Japan's Quest for Autonomy : National Security and Foreign Policy, 1930-1938 - Crowley, James B. (Book collections on Project MUSE., 2015)
A comprehensive and often controversial account of Japan's foreign and security policy before the Second World War based on War Crimes Trials materials, original Japanese sources, and detailed accounts by Japanese historians.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.